(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to identify to identify the level of kinetic binding capacity of the sample, and to identify the level of scoring skill to the research sample, and to identify the relationship between the kinetic linkage and skill scoring the surveyed sample the ability, and the researcher used thej descriptive survey manner, and sample research (85 ) player of the players Futsal clubs of different tests were applied to the sample for each club day dedicated to him was to extract statistics by the statistical program (spss) It was presented and analysis of the results was discussed and concluded the researcher has developed recommendations which contributes kinetic linkage scoring directly and a high level, can predict the kinetic link through the scoring, and the recommendations were: the adoption of the search results for learners and trainers as a reference for predicting the ability studied. Attention to the training of harmonic capacity through training and basic skills to suit every ability. Interest in the technical aspects of the special skills to relate to interoperability capabilities. Study different harmonic capabilities of different skills. Conduct studies and research similar and different event